The effect of a passive trunk exoskeleton on functional performance in healthy individuals. (October 2018) - Baltrusch, S.J.; van Dieën, J.H.; van Bennekom, C.A.M.; Houdijk, H.
Abstract: The objective of this study was to assess the effect of a passive trunk exoskeleton on functional performance for various work related tasks in healthy individuals. 18 healthy men performed 12 tasks. Functional performance in each task was assessed based on objective outcome measures and subjectively in terms of perceived task difficulty, local and general discomfort. Wearing the exoskeleton tended to increase objective performance in static forward bending, but decreased performance in tasks, such as walking, carrying and ladder climbing. A significant decrease was found in perceived task difficulty and local discomfort in the back in static forward bending, but a significant increase of perceived difficulty in several other tasks, like walking, squatting and wide standing. Especially tasks that involved hip flexion were perceived more difficult with the exoskeleton. Design improvements should include provisions to allow full range of motion of hips and trunk to increase versatility and user acceptance. Highlights: We assessed objective and subjective performance of a passive trunk exoskeleton. The exoskeleton decreased local discomfort in the back in static holding tasks. Tasks that involved hip flexion were perceived more difficult with the exoskeleton. Provision of full ROM is needed to increase versatility and user acceptance.